Obstetric factors associated with uterine rupture in mothers who deliver infants with cerebral palsy. (4th March 2021) - Hasegawa, Junichi; Ikeda, Tomoaki; Toyokawa, Satoshi; Jojima, Emi; Satoh, Shoji; Ichizuka, Kiyotake; Tamiya, Nanako; Nakai, Akihito; Fujimori, Keiya; Maeda, Tsugio; Takeda, Satoru; Suzuki, Hideaki; et al.
Abstract: Objective: The aim of the present study was to clarify the obstetric factors associated with uterine rupture in mothers who deliver infants with cerebral palsy (CP) in Japan. Methods: This retrospective case-cohort study reviewed the obstetric characteristics and clinical courses of mothers who experienced uterine rupture and compared those who delivered an infant with CP (cases) with those who delivered an infant without CP (cohort). Data were obtained from the Japan Obstetric Compensation System for CP database (27 cases) and the perinatal database of the Japan Society of Obstetrics and Gynecology (312 cohorts). The subjects included live singleton infants delivered between 2009 and 2014 with a birth weight ≥2000 g and gestation ≥33 weeks. Results: Augmentation was performed 33% in cases and 8% in cohorts ( p  < .001). The amount of bleeding during surgery was 1819 g in cases and 1096 g in cohorts ( p  < .001). Length of gestational weeks and neonatal birth weight were significantly higher and Apgar scores and umbilical arterial pH were lower in cases compared to cohorts ( p  < .001). In cases with CP, 11 cases of uterine rupture involved scarred uteruses. Seven were trial of labor after a previous cesarean. On one hand, 16 cases occurred in unscarred uteruses. Five of the uterine fundal pressure maneuvers and four of tachysystole due to excessive augmentation were reported in association with uterine rupture. Conclusion: Two-third of the relevant obstetric factors for CP associated with uterine rupture were iatrogenic. At least, to reduce CP resulting from delivery-related uterine rupture, reckless delivery management should be avoided.